2016
DOI: 10.1021/acs.chemmater.6b02239
|View full text |Cite
|
Sign up to set email alerts
|

Understanding The Fascinating Origins of CO2 Adsorption and Dynamics in MOFs

Abstract: Metal−organic frameworks (MOFs) have shown great promise for the adsorption and separation of gases, including the greenhouse gas CO 2 . In order to improve performance and realize practical applications for MOFs as CO 2 adsorbents, a deeper understanding of the number and type of CO 2 adsorption mechanisms must be unlocked, along with fine details of CO 2 motion within MOFs. Using several complementary characterization methods is a promising protocol for comprehensively investigating the various host− guest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 124 publications
3
97
0
1
Order By: Relevance
“…In particular, a low‐temperature 13 C SSNMR spectroscopic study of CO 2 ‐loaded CdSDB suggests that CO 2 occupies two nonequivalent sites in the CdSDB framework . In addition, single X‐ray diffraction of the CO 2 ‐loaded CdSDB framework confirmed that the two nonequivalent adsorption sites (labelled as C1A and C1B) are constituted by two different π pockets from the phenyl rings of the SDB ligands (Figure a, b) . As demonstrated by both SSNMR and single‐crystal XRD studies, the nature of the interaction between CO 2 molecules and both MOF frameworks is that the quadrupole moment of CO 2 interacts with the π electrons of the two phenyl rings .…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In particular, a low‐temperature 13 C SSNMR spectroscopic study of CO 2 ‐loaded CdSDB suggests that CO 2 occupies two nonequivalent sites in the CdSDB framework . In addition, single X‐ray diffraction of the CO 2 ‐loaded CdSDB framework confirmed that the two nonequivalent adsorption sites (labelled as C1A and C1B) are constituted by two different π pockets from the phenyl rings of the SDB ligands (Figure a, b) . As demonstrated by both SSNMR and single‐crystal XRD studies, the nature of the interaction between CO 2 molecules and both MOF frameworks is that the quadrupole moment of CO 2 interacts with the π electrons of the two phenyl rings .…”
Section: Resultsmentioning
confidence: 87%
“…However, the number of CO 2 adsorption sites and the nature of guest–host interactions may be substantially different from those at high pressures and can be efficiently tuned by external compression. In particular, a low‐temperature 13 C SSNMR spectroscopic study of CO 2 ‐loaded CdSDB suggests that CO 2 occupies two nonequivalent sites in the CdSDB framework . In addition, single X‐ray diffraction of the CO 2 ‐loaded CdSDB framework confirmed that the two nonequivalent adsorption sites (labelled as C1A and C1B) are constituted by two different π pockets from the phenyl rings of the SDB ligands (Figure a, b) .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Solid‐state NMR (SSNMR) spectroscopy is a sensitive probe of short‐range structures and can provide detailed information on the guest adsorption, structure, mobility, and host–guest interactions in MOFs ,,. NMR interactions are generally anisotropic and are affected by dynamics in a predictable manner, therefore, information regarding guest mobility and adsorption can be extracted from SSNMR spectra of gases within MOFs .…”
Section: Introductionmentioning
confidence: 99%